COVID-19-DRIVEN SOCIETAL SUSTAINABILITY IN THE APPAREL SUPPLY CHAIN: INSIGHT FROM MUSLIM-MAJORITY COUNTRIES - Mousa, Kawther; Ahmad, Muhammad Naveed; Sumarliah, Eli (IJIBE (International Journal of Islamic Business Ethics), 2022)
The current COVID-19 epidemic unveils the vulnerability in the apparel supply chain (ASC). Many workforces are facing future uncertainty due to pandemic-driven job losses. This study aims to comprehend the causes of societal sustainability deficiency in the ASC in Muslim-majority countries and propose strategies supporting a suitable improvement. Information gathered from experts using a qualitative research method; reveals that the primary cause of the lack of societal sustainability is the dominating power of several brands in the ASC. The usage of contract workforce and illegal subcontracting of apparel production also disrupt the protocol of societal compliance. Besides, the lack of application of Islamic ethics in business operations leads to poor labor conditions causing disruption in labor-societal security. The study proposes that it is imperative to adopt a sustainable procurement framework that integrates the sharing of disturbance risks among suppliers and brands post-COVID-19 crisis. It is also crucial to prohibit suppliers operate illegal subcontracting of apparel manufacture. Besides, brands’ order allocation plans and supplier selection must be adjusted to enable the workforce’s societal security. Contribution from labor unions and NGOs must be urged to achieve the grassroots level in community development schemes. As this study involves the Muslim-majority context, mitigation strategies from the Islamic ethics perspective are also considered helpful for solving societal sustainability issues in the ASC.